Berczeli Anzelm Károlyhoz - Garai István (Fond 380 Berczeli Anzelm Károly írói hagyatéka, 1968)
Fond 380 Berczeli Anzelm Károly írói hagyatéka > Berczeli Anzelm Károly levelezése > Berczeli Anzelm Károlyhoz írt levelek